Predictors of remission from PTSD symptoms after sexual and non-sexual trauma in the community: A mediated survival-analytic approach. (February 2018) - Müller, Mario; Ajdacic-Gross, Vladeta; Rodgers, Stephanie; Kleim, Birgit; Seifritz, Erich; Vetter, Stefan; Egger, Stephan T.; Rössler, Wulf; Castelao, Enrique; Preisig, Martin; Vandeleur, Caroline
Abstract: Epidemiological data on the chronicity of posttraumatic stress disorder (PTSD) symptoms in relation to trauma type and underlying pathways are rare. The current study explored how PTSD symptoms change over time across different trauma types and examined mediators of their persistence. A trauma-exposed community sample, whereof approximately one quarter met diagnostic criteria for PTSD, provided retrospective data on the duration of PTSD symptoms. Those who remitted and those who had not at the time of assessment were compared regarding worst trauma, symptom severity, comorbidity, demographic and treatment-seeking variables. Time to remission was estimated using Cox proportional hazard models including candidate predictors of remission. A mediated survival analysis was used to explore indirect pathways that explain trauma-specific differences in remission times. Both the full sample and PTSD subgroup were analyzed separately. Overall, lower socio-economic status, lifetime and childhood sexual trauma, symptom severity, comorbid depression and past treatment were associated with non- and longer remissions. PTSD avoidance symptoms and comorbid depression were found to mediate longer remission times after lifetime or childhood sexual trauma. Our findings provide insight into the mechanisms and complicating factors of remission from PTSD symptoms after trauma, which might have important implications for therapeutic interventions. Highlights: The present study examined predictors and mediators of persistence of PTSD symptoms. Individuals with PTSD had lower symptom remission rates than the full trauma sample. Those with PTSD were also slower to remit from their symptoms than the full sample. Sexual trauma and symptom severity were linked to non- or delayed remission. Comorbid depression and treatment history were linked to non- or delayed remission. Avoidance symptoms and secondary depression delayed remission after sexual trauma.